Writing as a craft: Re-considering teacher subject content knowledge for teaching writing - Myhill, Debra; Cremin, Teresa; Oliver, Lucy (Research papers in education, 2023)
The importance of teacher subject knowledge as key professional knowledge has been emphasised in successive studies over the past thirty years, yet there are very few empirical studies which address either content or pedagogical knowledge for teaching writing. At the same time, in a number of international jurisdictions, writing attainment lags behind reading attainment. This article addresses these concerns by considering what might constitute subject content knowledge for writing, and thus what might inform pedagogical interventions to improve achievements in writing. The article draws on an Arts Council-funded project in England, Teachers as Writers, a collaborative research project with the creative writing charity, Arvon. Drawing on qualitative data from nine professional writers, the article analyses how the writers communicated an understanding of writing as 'the craft of what we do' and articulated their craft knowledge during their encounters with teachers. The article proposes that subject content knowledge for writing might more helpfully be considered as craft knowledge, rather than as a body of factual knowledge, and presents a framework of five thematic themes through which to conceptualise this craft knowledge. These themes offer a way of thinking about craft knowledge as both text-oriented and writer-oriented.